Activated biochar and humic acid as additives in soluble phosphate fertilizer - Leite, Maurício Cunha Almeida (2019)
Therefore, the use of coating substances 1n fertilizers capable of preventing phosphorus (P) sorption 1n soil can be strategic to Increase the efficiency of these products. The present work was aimed at evaluating the use of humic acid and a chemically modified biochar as additives m granules of monoammonium phosphate (MAP), as well as to study P diffusivity, P release in soil and 1ts effect on plants growth. Biochar from eucalyptus sawdust was produced and chemically modified with zinc chloride, aluminum chloride and iron chloride, 1n order to select the biochar with the highest potential of P sorption. Zinc biochar (ZnBC) showed the highest sorptive potential and it was selected for further evaluated for sorption and desorption analysis. After evaluating the kinetic potential of sorption e desorption of P, the ZnBC was compared with humic acid (HA) as additives mn granules of phosphate fertilizer (MAPZnBC and MAPHA respectively) by mean of diffusivity trial, P release in soil and an agronomic experiment. It was observed that the treatments MAPHA and MAPZnBC did not effectively change the diffusivity, but were able to increase the contents of P-soil release in comparison with the control treatment (MAP) im the granulesphere soil. However, in the agronomic evaluation, the additives had no effect on the dry matter of the crops, and only MAPHA was able to increase the P uptake by the plants